COMPARISON OF THE ANNUAL POWER BALANCE OF PHOTOVOLTAIC MODULES - Bilčík, Matúš (Journal on Processing and Energy in Agriculture, 2020)
This article presents the results of a research study focusing on the effect of tilt angle changes on the power balance of photovoltaic (PV) systems. The objective of this study was to determine tilt-angle-induced differences in the power balance of two different types of photovoltaic modules: bifacial and monofacial. A comparison of the power balance results, obtained for the PV modules installed on the roof a building with tilt angles of 25° and 90°, was made. Ultimately, the simulation of power changes was performed for the modules installed on the roof with different black and white surfaces. The measurement data were collected using the solar invertors FRONIUS IG and the pyranometer CMP 11. The results obtained indicate that the PV system integrated into the building’s façade had a better power balance than the PV system installed on the building’s roof in the period from October to January. The power of the bifacial PV modules considered was found to be greater than that of the monofacial PV modules considered. The energy production of bifacial modules proved greatly dependent on the roof surface reflection coefficient.
Keywords: PV system, tilt angle, PV construction, year